Neurosurgical patients' morbidity and mortality during the COVID-19 pandemic: An integrated review (Research, Society and Development, 2023)
Objective: To assess mortality among neurosurgical patients during the COVID-19 pandemic period. Methods: This study entails an integrative literature review conducted by querying predefined descriptors in databases including Science Direct, PubMed®, and the Biblioteca virtual em saúde. Results: A total of 777 articles were identified. After applying inclusion and exclusion criteria, 14 studies were selected to constitute the foundation of this review. A disparity emerged across studies concerning alterations in mortality rates during the COVID-19 pandemic. While the majority of articles (n = 6) reported an increase in mortality, four studies observed no change in mortality rates when comparing the pandemic period with the pre/post-pandemic period. Regarding the number of neurosurgical procedures, a variable decline was observed across studies, ranging between 11.5% and 43%. The majority of articles documented a rise in postoperative complications during the pandemic. Conclusion: A significant impact of the SARS-CoV-2 pandemic on the surgical context was observed, as there was a notable reduction in the number of surgeries performed, leading to an increase in postoperative complications and potentially the mortality rate.